KINERJA DINAS PEHUBUNGAN KOTA BALIKPAPAN - , MUHAMMAD REZHA; , Dr. Bevaola Kusumasari, M.Si ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Traffic is a big serious problems for the government, traffic planning, layout and vehicle congestion is routine evaluation for local government transportation agencies in this regard. Balikpapan is a growing city in eastern Borneo which became one of the economic centers in the heart of East Kalimantan. Department of transportation Balikpapan city was one of the best transportation services in Indonesia. This study will evaluate the performance of the transportation department of the city of Balikpapan. The fieldwork includes three aspects, namely accountability, teamwork and relationships between leaders and subordinates. Accountability of the employees seen on the amount of time, time intensity, and number of employees. Cooperation team assessed from the aspect of cooperation and coordination, while relationship management and employee empowerment challenge and cooperation between the two. All these aspects can affect the performance of departmentof transportation Balikpapan city